Corporate diversification and firm value: evidence from emerging markets - Akben Selçuk, Elif. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2012., 2012)
The objective of this dissertation is to investigate the impact of corporate diversification on firm value in emerging markets. To answer the research question, three analyses are conducted. First, using data from nine countries, namely, Brazil, Chile, Indonesia, Malaysia, Philippines, Poland, South Africa, Thailand, and Turkey for the years 2005-2010, we run a panel data regression. The results show that diversified firms in these countries trade at a premium. Second, in order to analyze the results for Turkish companies more closely, we investigate the moderating role of business group affiliation for the relationship between diversification and value. Using data from 189 Turkish firms for the period between 2005 and 2010, we find that firm level diversification is beneficial only for firms that do not belong to groups. For group members, firm level diversification does not provide an additional advantage. Finally, in order to analyze the diversification-value relationship from a different perspective, we conduct an event study consisting of 100 acquisition announcements made by Turkish companies between 2005 and 2011. The results show higher bidder returns for diversifying acquisitions compared to focused acquisitions. The results of this study are consistent with internal capital markets hypothesis and institution-based theory of diversification.|Keywords : Corporate diversification, firm value, diversification discount and premium, emerging markets, Turkey.
Keywords: Diversification in industry.; Corporate governance.